Effect of different rootstocks on productivity and quality of 'Cabernet Sauvignon' grapevine produced in high altitude regions of Santa Catarina State, Brazil - Brighenti A.F.* (2012)
Rootstocks can affect plant growth, productivity, physical and chemical characteristics and therefore, wine composition. The objective of this study was to evaluate the productivity and the quality of 'Cabernet Sauvignon' grapevine grafted on Paulsen 1103 (V. berlandieri × V. rupestris), Couderc 3309 and 101-14 Mgt (V. riparia × V. rupestris). The experiment was conducted in a vineyard located at the city of Painel (28°01'02"S and 50°08'57"W, altitude 1200 m), in Santa Catarina State, Brazil. The experimental design was randomized blocks, with four blocks and 20 plants per plot. The plants were five years old and conducted in vertical shooting positioning trellis, the experiment was evaluated at the seasons 2008 and 2009. The variables analysed were productivity (kg plant-1 and ton ha -1), cluster weight (g), 50 berries weight (g), berry diameter (mm), cluster length (cm), number of berries per cluster, leaf area (m2), pruning weight removed (kg), Ravaz Index, anthocyanins (mg L-1), total polyphenols, tannins, pH, total soluble solids and acidity (meq L-1). Data were submitted to analysis of variance and Tukey's test (5% probability). In both seasons, the lowest yields were observed in the rootstock 1130 P and the highest cluster weight in 3309 C. In high altitudes regions of southern Brazil rootstocks of low to intermediate vigor, like Couderc 3309 and 101-14 Mgt, provide better balance between vine reproductive and vegetative activity and influence positively on vine yield and grape quality for production of 'Cabernet Sauvignon' red wines.